Elite or emasculated males? A discussion of Eunuchs in the Hebrew Bible and their place within a phallocentric society - Barnett, Elizabeth (2022)
This thesis centres around eunuchs in the Hebrew Bible, discussing the various ranks of masculinity they were placed in, the ideas surrounding their position within a ‘third gender’ category, and their place in religion, society, and relationships. This research has been briefly discussed in some aspects of previous Hebrew Bible scholarship, and some themes have been touched on, e.g., the relationship between disability studies and eunuchs. However, the topic of ancient Israelite eunuchs is one that is yet to be explored in great depth. This thesis studies biblical texts, along with commentaries and thematic studies. My results highlight that, perhaps, the label of ‘third gender’ is not appropriate when referring to eunuchs due to the lack of evidence suggesting they identified with anything except their birth gender, and that a more suitable label would be an effeminate or inferior man. Eunuchs maintained various roles that both ancient Israelite men and women would carry out, however this cannot be sufficient reasoning for a ‘third gender’ category.